Effect of selected fungicides on growth and development of Exserohilum longirostratum - Gooi, Seow Ping.
Exserohium longirostratum isolated from Rottboellia cochinchinensis (itc grass) has been determined as a potential bioherbicide for itch grass. This fungus has the potential to be used as a sole control agent or be tank-mixed with chemical herbicides, however the compatibility of this fungus with fungicides are still unknow. Interaction between E. longirostrratum and selected fungicides were studied in the laboratory. E. longirostratum grew well in all concentrations of Benlate but radial growth was inhibited in Score, Topper and Dithane at all concentrations. Fungal biomass productions in Benlate were as high as in control, and were inhibited in other fungicides tested. The conidia germinations were very low at all concentrations in Dithane. However in Topper and Score, conidia germination was inversely related with concentrations tested. Conidia production were very low in Dithane, Score and Topper compared to Benlate. Findings in this study indicate that Score, Topper and Dithane were incompatible with E. longirostratum, thus should not be sprayed together with E. longirostratum. Dithane is an excellent fungicide for controlling E. longirostratum should this fungus infects crop plants.